The Impact of Emotional Intelligence, Organizational Climate, and Moral Behavior on The Performance of State Civil Services at The Forestry Service of North Sumatra, Medan City - Hasibuan, Alamsyah; Hutasuhut, Julianto; Syamsuri, Abd. Rasyid; Fikri, Muhammad Hilman (Garuda Prestasi Nusantara Consulting, 2022)
This study intends to examine how the state civil apparatus at the Forestry Service of North Sumatra, Medan City, performs in relation to emotional intelligence, organizational climate, and ethical behavior. This study used a quantitative research methodology. Pre-research completed in March 2022 serves as the foundation for the remainder of this study. Observation, documentation studies, and questionnaires were the data collection methods employed. The population of this study consisted of up to 60 workers from the Forestry Service of North Sumatra in Medan City. A saturation sampling approach was used to sample all populations. Multiple linear regression is the analytical technique employed, and the SPSS (Statistical Product Software Solution) program is used. The study's findings demonstrate that emotional intelligence significantly and positive affects the effectiveness of the State Civil Apparatus. The performance of the State Civil Apparatus is positively and significantly impacted by organizational climate. The State Civil Apparatus performs better and much better when ethical behavior is followed. The State Civil Apparatus performs better when emotional intelligence, organizational atmosphere, and ethical behavior are all present. According to this study's coefficient of determination (R2) of 0.743, ethical conduct, organizational atmosphere, and emotional intelligence together account for 74.3% of the State Civil Apparatus' performance. Keywords: Emotional Intelligence, Organizational Climate, Ethical Behavior, Performance of State Civil Apparatus